Dairy quality attributes, consumer preferences, and price premiums in Ethiopia: A review - Shete, Maru; Kassie, Girma T.; Yilma, Zelalem; Abate, Gashaw T.; Minten, Bart (CGIAR System Organization, 2025)
Ethiopia’s dairy sector is dominated by smallholder mixed crop–livestock systems with relatively large herds but persistently low productivity. This productivity gap underscores the sector’s untapped potential and the need to address constraints across the value chain. Quality and safety problems are widespread: microbial contamination, adulteration, and poor handling – worsened by limited cold-chain infrastructure – pose serious public health risks. Traditional open markets remain the main outlets, supplying fresh, flavourful, high-fat products that consumers prefer and can afford, but usually without assured safety or quality. Strong preferences for raw over pasteurized milk further depress demand for quality-enhanced products and weaken incentives for improved practices. Market structures rarely reward higher quality, as price premiums and willingness to pay for upgraded products are low, discouraging investment in better inputs, handling, and processing. Policy and institutional weaknesses – including weak input and service systems, poor enforcement of safety standards, limited value addition, and the dominance of informal markets – further constrain development. Together, these factors trap the sector in a low-productivity, low-quality equilibrium. Transforming the sector is essential and feasible, but will require stronger regulatory enforcement, expanded quality assurance, and quality-based pricing that realigns incentives, raises productivity, improves milk safety, and supports a more competitive, sustainable dairy industry.